Step
*
1
of Lemma
sine0
1. Σi.-1^i * (r0^(2 * i) + 1)/((2 * i) + 1)! = sine(r0)
⊢ sine(r0) = r0
BY
{ Assert ⌜Σi.-1^i * (r0^(2 * i) + 1)/((2 * i) + 1)! = r0⌝⋅ }
1
.....assertion..... 
1. Σi.-1^i * (r0^(2 * i) + 1)/((2 * i) + 1)! = sine(r0)
⊢ Σi.-1^i * (r0^(2 * i) + 1)/((2 * i) + 1)! = r0
2
1. Σi.-1^i * (r0^(2 * i) + 1)/((2 * i) + 1)! = sine(r0)
2. Σi.-1^i * (r0^(2 * i) + 1)/((2 * i) + 1)! = r0
⊢ sine(r0) = r0
Latex:
Latex:
1.  \mSigma{}i.-1\^{}i  *  (r0\^{}(2  *  i)  +  1)/((2  *  i)  +  1)!  =  sine(r0)
\mvdash{}  sine(r0)  =  r0
By
Latex:
Assert  \mkleeneopen{}\mSigma{}i.-1\^{}i  *  (r0\^{}(2  *  i)  +  1)/((2  *  i)  +  1)!  =  r0\mkleeneclose{}\mcdot{}
Home
Index